Building Resilience In Bullying Victims Through Guidance And Counseling Services: A Case Study At SMPN 23 Tangerang - Ahmad Suja’i; Riesta Gita Cahyani (TA'DIBAN, 2026)
This study aims to describe the forms of bullying, victims' self-esteem, the psychosocial impacts experienced, and the strategies used by guidance and counseling (BK) teachers in building student resilience at SMPN 23 Tangerang. The study used a qualitative approach with a case study design involving two BK teachers, members of the PIK-R (Regional Student Activity Unit), and four student victims of bullying. Data were collected through observation, in-depth interviews, and documentation, then analyzed thematically. The results showed that victims with low to moderate self-esteem experienced fear, social trauma, decreased motivation to learn, social isolation, and suicidal thoughts. BK teachers developed resilience through individual counseling, strengthening social support, emotional support, and collaboration with parents. The study findings emphasize the importance of resilience-based BK services to support victim recovery and create a safe, inclusive, and supportive school environment.